An exploratory study on the use of Photovoice as a method for approaching FASD prevention in the Northwest Territories - Badry, Dorothy; Wight Felske, Aileen (First Peoples Child & Family Review, 2013)
The Brightening Our Home Fires (BOHF) Project was a project that took place in four communities in the Northwest Territories (NT) from 2011-2012. The purpose of this project was to explore the issue of Fetal Alcohol Spectrum Disorder (FASD) prevention as a health concern in the NT, and to develop an approach that was meaningful for women participants. The intent of the project was to develop a culturally-responsive intervention study addressing links between trauma, and FASD prevention from a social determinant of women’s health perspective through a Participatory Action Research framework. While the project was intended to explore and inform on the topic of FASD prevention work, the primary research question was: What does health and healing look like for you in your community? Thirty women from four communities participated in this project: Yellowknife, Lutsel ‘ke, Behchokö, and Ulukhaktok. This research had differing impacts on participants but an overarching construct was that participation in Photovoice supported women to see their lives in new ways and to reflect upon different struggles and possibilities. Engaging in this research was intended to build relationships, develop community based research partnerships and intended to develop a framework for informing services and practice responses, or enhancements to current service delivery frameworks around FASD prevention and related health concerns.